Penanaman Mangrove untuk menjaga Pelestarian ekosistem pantai di Desa Nagalawan Kecamatan Perbaungan Kabupaten Serdang Bedagai - Erlita Chaniago; Aisyah Lubis; Iwan Hasrizart (LPPM Universitas Al-Azhar medan, 2024)
Mangrove forests on the coast are expected to maintain coastal stability. Mangrove trees can preserve coastal ecosystems, where it is known that one of the functions of mangroves is that they are a place for flora and fauna to live. Apart from that, mangroves also have the function of maintaining water and air quality and also function to maintain climate and weather. The role of mangroves in maintaining the balance of the ecosystem is so important, so it is appropriate for students of the agricultural faculty of the Agrotechnology study program to take an active role in preserving mangrove forests. It is hoped that in the future this will continue for other coastal areas in the North Sumatra region to maintain the stability of the coastal ecosystem